To factor 3x + 9 you should know that 3 is a common factor of both 3 and 9, so you can factor 3 out in both numbers like this.
3x + 9
3(x + 3)
When you factor out 3 on both numbers you should know that 3 X 3 = 9 and since you factored out 3 there would be another 3 left so you would have the answer: 3(x + 3)
Here is another equation that might help:
24x + 36
Since 12 is a common factor of both numbers, factor 12 out of the equation:
12 (2x + 3)
You know that 12 x 2 = 24 and that 12 x 3 = 36
And since you can't factor out anymore numbers because 2 and 3 doesn't have any common factors with each other you get the answer:
12 (2x + 3)
Answer:
C
Step-by-step explanation:
Since the triangles are similar then the ratios of corresponding sides are equal, that is
=
, substituting values
=
( cross- multiply )
21x = 7(24 - x) ← distribute
21x = 168 - 7x ( add 7x to both sides )
28x = 168 ( divide both sides by 28 )
x = 6 → C
Answer:
B, the square root of 3
Step-by-step explanation:
6/10
3/5
24/40
36/60
48/80
60/100